Effects of Adding Tricalcium Silicate Nanoparticles to the Universal G2 Bond Adhesive as Self‐Etch Mode on the Shear Bond Strength to the Orthodontic Bracket - Yasir R. Al‐Labban; Mehdi Alrubayee; Syed Jaffar Abbas Zaidi; Shakeel Kazmi (Clinical and Experimental Dental Research)
ABSTRACT Objective This study investigated the effects of adding tricalcium silicate nanoparticles (TCSNp) to the universal G2 bond adhesive (G2BU) in self‐etch (SE) mode on shear bond strength (SBS) to orthodontic brackets, cytotoxicity, and degree of conversion (DC). Material and Methods A total of 176 human teeth were divided into four groups based on TCSNp concentration in G2BU adhesive: 0% (control), 1%, 3%, and 5%. The G2BU adhesive consists of a hydrophilic primer (P) and a hydrophobic bonding agent (2B). TCSNp were added to the 2B component by mixing 0.1, 0.3, and 0.5 g of TCSNp with 9.9, 9.7, and 9.5 g of 2B, respectively. SBS was assessed after 24 h of water storage and 5000 thermocycles using a universal testing machine. Cytotoxicity was evaluated using the MTT assay on rat embryo fibroblast cells, and DC was measured using fourier‐transform infrared spectroscopy. Statistical analysis included one‐way ANOVA and Tukey's post‐hoc test, with significance set at p < 0.05. Results After 24 h, mean SBS values were 15.58 MPa (control), 13.66 MPa (1% TCSNp), 15.99 MPa (3% TCSNp), and 12.04 MPa (5% TCSNp). After 5000 thermocycles, SBS values decreased to 12.91 MPa (control), 12.42 MPa (1% TCSNp), 11.11 MPa (3% TCSNp), and 10.21 MPa (5% TCSNp). ANOVA showed significant differences between groups (p < 0.05), except between the control and 3% TCSNp groups. Cell viability increased with higher TCSNp concentrations, with significant differences at 72 h between control and 5% TCSNp groups (p = 0.014). Mean DC values were 51.66% (control), 49.33% (1% TCSNp), 49.66% (3% TCSNp), and 48% (5% TCSNp). ANOVA indicated no significant differences between groups. Conclusions Adding TCSNp to G2BU in SE mode maintains clinically acceptable SBS levels and enhances cytocompatibility. Higher TCSNp concentrations may reduce SBS and DC slightly. Further studies are needed to evaluate long‐term effects.